Individuellt uppmärksammade kunder - Bauer Barsby,Filip; Wångdahl,Jenny (2017)
The aim of this study is to contribute to increased knowledge within the field of strategic communication in general and personalized marketing in particular. More specifically, the authors intend to provide a framework that would allow for a less hierarchical relationship between companies within the marketing industry and their customers. To achieve this purpose, the following research question was con- structed: What are the Swedish students experience, knowledge and attitude to- wards personalized marketing that is based on their behavioural patterns online? The empirical data was collected through 20 semi-structured interviews with young academics. This target group was selected as it was considered best to un- derstand a target group that is thought to be critical in nature. Their responses were then analysed primarily based on theories of people's behavioural patterns in differ- ent situations. The analysis shows that respondents have a positive attitude towards personal- ized marketing as a theoretical concept, but are dissatisfied with how the data col- lection is practiced by today's marketers. In addition, it can be demonstrated that customers seek higher transparency and control over which information is collected and how it is thereafter spread by the companies. The findings of this study has two important implications for companies using personalised marketing: companies should focus more on transparent communica- tion when discussing how they handle customers' data as well as reward those cus- tomers who actively share information. This way, companies can encourage cus- tomers to initiate relationships with them, thus encouraging a more pleasant ex- change. In addition to this, we would like to certify that both authors has been partici- pating to this study at equal parts in every section of it.
Keywords: individanpassad marknadsföring; företagsförtroende; transparens; integritet; bete- endemönster online